The Investigation of the Distribution of ABO/Rh Blood Group in Hospitalized COVID‐19 Patients and Its Association With Disease Severity, Clinical Outcomes, Lab Tests, and Radiologic Findings - Abolfazl Zendehdel; Azadeh Asoodeh; Mohsen Ansari; SaeidReza JamaliMoghaddamsiyahkali (Health Science Reports)
ABSTRACT Background and Aims it is important to identify patients at higher risk for severity and poor outcomes of COVID‐19 infection, to have better disease management and pandemic control. In this study, we aimed to assess the distribution of ABO and Rh blood groups in hospitalized COVID‐19 infected patients and demonstrate its association with severity and outcomes of the disease. Methods This is a cross‐sectional study at Ziaeian Specialist Hospital, in Tehran, Iran. Of all confirmed COVID‐19 infected patients who were admitted to this hospital, 273 patients were enrolled in this study and categorized based on their disease severity or clinical outcomes including intensive care unit (ICU) admission, need for mechanical ventilation and mortality. The distribution of ABO and Rh blood groups was assessed and compared between different groups, to investigate the association of blood group types with disease severity or outcomes. Also, the study population was categorized based on their blood group types to demonstrate the association of laboratory parameters, radiologic findings, and length of hospitalization with blood groups. Sex, age and underlying disease were adjusted in the final model by multivariate regression analysis. Results This study showed that Blood group A (35.9%) was the most prevalent among hospitalized COVID‐19 patients followed by O (34.8%), B (21.6%), and AB (7.7%) (A > O > B > AB). ABO and Rh blood group was not associated with disease severity, need for mechanical ventilation, or ICU admission, while blood group B was associated with an increased risk of death in comparison with type O, in hospitalized COVID‐19 patients (p = 0.02). The number of patients with severe levels of C‐reactive protein (CRP) test results was lower in O blood group patients in comparison with non‐O blood groups (p = 0.01). Conclusion No significant association was found between blood groups and other lab tests, radiologic findings, and length of hospitalization.